Home > Algebra calculators > If a/b=c/d=e/f then prove that (2a+3c-4e)/(2b+3d-4f)=(5a-4c+3e)/(5b-4d+3f) calculator

Solve any problem
(step by step solutions)
Input table (Matrix, Statistics)
Mode :
SolutionHelp
Solution
Find In ratio and proportion, if x/(b^2-c^2)=y/(c^2-a^2)=z/(a^2-b^2) then prove that x+y+z=0

Solution:
Your problem `->` In ratio and proportion, if x/(b^2-c^2)=y/(c^2-a^2)=z/(a^2-b^2) then prove that x+y+z=0


`x/(b^2-c^2)=y/(c^2-a^2)=z/(a^2-b^2)`

Suppose, `x/(b^2-c^2)=y/(c^2-a^2)=z/(a^2-b^2)=k` (say)

`:. x=b^2k-c^2k,y=c^2k-a^2k,z=a^2k-b^2k`

Now LHS`=x+y+z`

`=(b^2k-c^2k)+(c^2k-a^2k)+(a^2k-b^2k)`

`=0`

`=`RHS






Solution provided by AtoZmath.com
Any wrong solution, solution improvement, feedback then Submit Here
Want to know about AtoZmath.com and me
  
 

Share with your friends
 
Copyright © 2018. All rights reserved. Terms, Privacy